A Metadiscursive Analysis of Arabic Religious Discourse. (25th February 2019) - Abdel-Moety, Doha Mahmoud
Abstract: The present study is concerned with Arabic religious discourse. It aims at investigating the distribution, use and function of reflexive metadiscourse in this genre. It also attempts to reveal the ways in which these elements are linguistically structured. Moreover, the study addresses the question of applying a model of metadiscourse in academic English to religious discourse. It applies a qualitative analysis with a simple quantification. It adopts a framework that draws on Ädel's (2010) model of metadiscourse in academic English. Results of the study show that Arabic religious discourse exemplified in religious sermons is highly metadiscursive. Both metatext and audience interaction categories of reflexive metadiscourse are employed in the sermon under investigation. The discourse functions under these categories are distributed throughout the five identified sections of the sermon. Results also indicate that there are discrepancies in the number of their occurrences in the sermon. The discourse functions under the category of audience interaction are more common in the sermon than the discourse functions under the metatext category. Finally, the study shows that the model of reflexive metadiscourse in academic English can be successfully applied to Arabic religious discourse. These findings reflect the communicative and engagement nature of Arabic religious sermons and call for paying special attention to metalinguistic functions within the genre of religious discourse.